Adaptasi Elemen-Elemen Pemasaran Di Dalam Pengurusan Pusat Sumber Sekolah - Rohana, Talib (1999)
The purpose of this study was to identify the factors that have great influence over the usage of teaching aids among teachers. There were lots of researches being carried out regarding the matter, but the situation remains the same as before. Therefore something should be done towards the management of resource center because resource center is the supplier of teaching aids. The research was to test the factors that could help in enhancing teachers to use teaching aids. It was further testing the perception of the teachers in the adaptation of marketing elements in the management of resource center. The elements focused were customer orientation, location, accessibility and communication. The research was carried out in two manners. First, an exploratory study was carried out to identify the problems that teachers are facing in the usage of teaching aids in schools. Second, a set of questionnaire was administered to collect data from teachers regarding their perception on the marketing elements in resource center management. Data were analyzed by using the descriptive statistics and inferential statistics. The results showed that the teachers perception on the four marketing elements which are customer orientation, accessibility, location/place and communication were highly positive. The observations seemed similar among all categories of teachers. There was no significant difference in the perception towards the marketing elements based on teachers’ background factors.